Recombination of B- and T-cell epitope-rich loci from Aedes- and Culex-borne flaviviruses shapes Zika virus epidemiology - Gaunt, Michael W.; Wilder-Smith, Annelies (Antiviral research, 2020)
Sporadic human Zika virus (ZIKV) infections have been recorded in Africa and Asia since the 1950s. Major epidemics occurred only after ZIKV emerged in the Pacific islands and spread to the Americas. Specific biological determinants of the explosive epidemic nature of ZIKV have not been identified. Phylogenetic studies revealed incongruence in ZIKV placement in relation to Aedes-borne dengue viruses (DENV) and Culex-borne flaviviruses. We hypothesized that this incongruence reflects interspecies recombination resulting in ZIKV evasion of cross-protective T-cell immunity. We investigated ZIKV phylogenetic incongruence in relation to: DENV T-cell epitope maps experimentally identified ex vivo, published B-cell epitope loci, and CD8+ T-cell epitopes predicted in silico for mosquito-borne flaviviruses. Our findings demonstrate that the ZIKV proteome is a hybrid of Aedes-borne DENV proteins interspersed amongst Culex-borne flavivirus proteins derived through independent interspecies recombination events. These analyses infer that DENV-associated proteins in the ZIKV hybrid proteome generated immunodominant human B-cell responses, whereas ZIKV recombinant derived Culex-borne flavivirus-associated proteins generated immunodominant CD8+ and/or CD4+ T-cell responses. In silico CD8+ T-cell epitope ZIKV cross-reactive prediction analyses verified this observation. We propose that by acquiring cytotoxic T-cell epitope-rich regions from Culex-borne flaviviruses, ZIKV evaded DENV-generated T-cell immune cross-protection. Thus, Culex-borne flaviviruses, including West Nile virus and Japanese encephalitis virus, might induce cross-protective T-cell responses against ZIKV. This would explain why explosive ZIKV epidemics occurred in DENV-endemic regions of Micronesia, Polynesia and the Americas where Culex-borne flavivirus outbreaks are infrequent and why ZIKV did not cause major epidemics in Asia where Culex-borne flaviviruses are widespread.
Available online 16 December 2019
Gesehen am 08.07.2020